Photobiomodulation Therapy Plus Usual Care Is Better than Usual Care Alone for Plantar Fasciitis: A Randomized Controlled Trial - Ann K Ketz; Juanita Anders; Judy Orina; Betty Garner; Misty Hull; Nicholas Koreerat; Jeff Sorensen; Candice Turner; James Johnson (International Journal of Sports Physical Therapy)
# Background